2015
DOI: 10.1097/qai.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Operational Research

Abstract: Background Current treatment guidelines for HIV infection recommend routine CD4+ lymphocyte (CD4) count monitoring in patients with viral suppression. This may have a limited impact on influencing care as clinically meaningful CD4 decline rarely occurs during viral suppression. Methods In a regional HIV observational cohort in the Asia-Pacific, patients with viral suppression (2 consecutive viral loads <400 copies/mL) and a CD4 count ≥200 cells/μL who had CD4 testing 6 monthly were analyzed. Main study endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…According to national guidelines, these tests have to be done on a 6-month basis [ 24 , 25 ]. Recent findings showed that annual monitoring of CD4 instead of every 6 months in persons with a CD4 above 250 cells/mm 3 was sufficient to detect any clinical problem early enough [ 26 ]. Such results, associated with the fact that new guidelines suggest starting HAART when CD4 reaches 500 cells/mm 3 [ 1 ], instead of previously indicated levels of 250 or 350 cells/mm 3 , will probably reduce the frequency of CD4 tests in PLWHA in their routine follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…According to national guidelines, these tests have to be done on a 6-month basis [ 24 , 25 ]. Recent findings showed that annual monitoring of CD4 instead of every 6 months in persons with a CD4 above 250 cells/mm 3 was sufficient to detect any clinical problem early enough [ 26 ]. Such results, associated with the fact that new guidelines suggest starting HAART when CD4 reaches 500 cells/mm 3 [ 1 ], instead of previously indicated levels of 250 or 350 cells/mm 3 , will probably reduce the frequency of CD4 tests in PLWHA in their routine follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…From a total of 1117 titles screened, 12 published studies [35,1220] were included, representing 20,297 patients. Investigators on one study among adults [20] provided additional data on children (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Investigators on one study among adults [20] provided additional data on children (Figure 1). A large initial number of titles were screened because no highly sensitive search strategy could be reliably used to identify the studies of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, however, when we repeated our analysis using only one data point for each patient, we found essentially the same results: 2 years after entering the cohort, 72.2%, 93.4%, and 98.3% (vs. 71.6%, 93.4%, and 98.1%) of those with initial CD4 cell counts of 200–349, 350–499, and ≥500 cells per cubic millimeter, respectively, maintained CD4 ≥200 cells per cubic millimeter. Also, in contrast with at least 1 other previous analysis, 15 we used a single CD4 drop to <200 as an endpoint. However, in an additional analysis (not shown) using a “confirmed” CD4 drop <200 (ie, 2 CD4 cell counts <200), the findings are even more robust: 2 years after entering the cohort, 94.9%, 99.2%, and 99.8% of those with initial CD4 cell counts of 200–349, 350–499, and ≥500 cells per cubic millimeter, respectively, maintained CD4 ≥200 cells per cubic millimeter.…”
Section: Discussionmentioning
confidence: 99%
“…Even more recently, in an observational cohort in the Asia–Pacific region, there was no significant difference in time to a confirmed CD4 <200 cells per cubic millimeter between biannual and annual CD4 measurement cohorts. 15 This mounting evidence was reflected in 2014 US guidelines proposing that CD4 count monitoring for stable virologically suppressed patients with CD4 counts consistently between 300 and 500 be conducted annually; the guidelines considered CD4 count monitoring for stable virologically suppressed patients with CD4 counts consistently >500 cells per cubic millimeter to be optional. 2…”
Section: Introductionmentioning
confidence: 99%